Investing in real estate - Eldred, Gary W. (John Wiley & Sons, Inc., 2012)
"To explore and illustrate contemporary and evolving market conditions and investment opportunities, this newly revised edition will include the following: 1. Provide historical/cyclical context to emphasize the unprecedented combination of bargain pricing and near record low interest rates now available in most cities. 2. Show how to meet and exceed today's changed loan underwriting standards. (Yes, loans are widely available-but readers/would-be investors must learn how to navigate the maze). 3. Discuss effective ways to successfully negotiate below-market prices with banks, distressed owners/mortgagors, and government agencies (HUD, FHA, Fannie, Freddie, etc.) 4. Reveal methods that will make sure your appraisal comes in at the value you want/need for loan approval. 5. Explain how to legally and ethically use easier/low down payment, owner-occupied financing to acquire investment properties. 6. Guide readers through the new procedures and processes used to acquire REOs (relatively) quickly and on favorable terms as well as illustrate how to structure and complete short sales on favorable terms.7. How to find motivated sellers and/or market properties through social media. 8. Capitalize on the low CD rate environment to persuade sellers to offer OWC property financing-indeed, a large and growing number of sellers need no persuasion. OWC financing is being offered by tens of thousands of sellers already. 9. Learn how to acquire properties through buying debt, subject-to agreements, and loan assumptions. (Yes, they are still available when you know where to look).10. Discuss why today's prices (contrary to media mis-statements and err-prone commentators) are sure to increase substantially and how to identify the properties and locations that will experience the highest rates of appreciation.In addition to the above (and many other) revisions that are especially crafted to address the new opportunities and challenges that will exist for the next several years, this 7th edition will achieve elevated standards for clarity, application, and time-tested investment principles and practices (p&p which were often forgotten or ignored during the boom years)"--